Direct Growth of Highly Conductive Large‐Area Stretchable Graphene. Issue 7 (1st February 2021) - Han, Yire; Park, Byeong‐Ju; Eom, Ji‐Ho; Jella, Venkatraju; Ippili, Swathi; Pammi, S. V. N.; Choi, Jin‐Seok; Ha, Hyunwoo; Choi, Hyuk; Jeon, Cheolho; Park, Kangho; Jung, Hee‐Tae; et al.
Abstract: The direct synthesis of inherently defect‐free, large‐area graphene on flexible substrates is a key technology for soft electronic devices. In the present work, in situ plasma‐assisted thermal chemical vapor deposition is implemented in order to synthesize 4 in. diameter high‐quality graphene directly on 10 nm thick Ti‐buffered substrates at 100 °C. The in situ synthesized monolayer graphene displays outstanding stretching properties coupled with low sheet resistance. Further improved mechanical and electronic performances are achieved by the in situ multi‐stacking of graphene. The four‐layered graphene multi‐stack is shown to display an ultralow resistance of ≈6 Ω sq −1, which is consistently maintained during the harsh repeat stretching tests and is assisted by self‐ p ‐doping under ambient conditions. Graphene‐field effect transistors fabricated on polydimethylsiloxane substrates reveal an unprecedented hole mobility of ≈21 000 cm 2 V −1 s −1 at a gate voltage of −4 V, irrespective of the channel length, which is consistently maintained during the repeat stretching test of 5000 cycles at 140% parallel strain. Abstract : Averaged mobility of 42 GTO‐FET (field‐effect transistor) devices indicates high hole and electron mobilities of 21 000 and 12 000 cm 2 V −1 s −1, respectively, at V GS = ± 4 V. The Ti–O–C interfacial layer indicated by the density functional theory‐predicted GTO model produces the unprecedented stretchability of the GTO‐FETs during 5000 cycles of parallel stretching of up to 140% strain.